CNNM2-Related Disorders: Phenotype and Its Severity Were Associated With the Mode of Inheritance - Zhang, Han; Wu, Ye; Jiang, Yuwu (Frontiers in Pediatrics, 2021)
CNNM2 (Cystathionine-β-synthase-pair Domain Divalent Metal Cation Transport Mediator 2) pathogenic variants have been reported to cause hypomagnesemia, epilepsy, and intellectual disability/developmental delay (ID/DD). We identified two new cases with CNNM2 novel de novo pathogenic variants, c.814T>C and c.976G>C. They both presented with infantile-onset epilepsy with developmental delay and hypomagnesemia refractory to magnesium supplementation. To date, 21 cases with CNNM2-related disorders have been reported. We combined all 23 cases to analyze the features of CNNM2-related disorders. The phenotypes can be classified into 3 types: type 1-autosomal dominant (AD) inherited simple hypomagnesemia, type 2-AD inherited hypomagnesemia with epilepsy and ID/DD, and type 3-autosomal recessive (AR) inherited hypomagnesemia with epilepsy and ID/DD. All five type 1 cases had no epilepsy or ID/DD; they all had hypomagnesemia and three of them presented with symptoms secondary to hypomagnesemia. 15 type 2 patients could have ID/DD and seizures which can be controlled with antiseizure medications (ASMs); their variations clustered in the DUF21 domain of CNNM2. All three type 3 patients had seizures from 1-6 days after birth; the seizures were refractory, and 1/3 had status epilepticus; ID/DD in these AR-inherited cases were more severe than AD-inherited cases; they all had abnormalities of brain magnetic resonance imaging (MRI). Except for 1 patient whose serum magnesium was the lower limit of normal, others had definite hypomagnesemia. Hypomagnesemia could be improved after magnesium supplement but could not be recovered normal. Variations in CBS2 domain may be related to lower serum magnesium. However, there was no significant difference in the level of serum magnesium among the patients with three different types of CNNM2-related disorders. The severity of different phenotypes was therefore not explained by decreased serum magnesium. We expanded the spectrum of CNNM2 variants and classified the phenotypes of CNNM2-related disorders into three types. We found that DUF21 domain variations were most associated with CNNM2-related central nervous system phenotypes, whereas hypomagnesemia was more pronounced in patients with CBS2 domain variations, and AR-inherited CNNM2-related disorders had the most severe phenotype. These results provide important clues for further functional studies of CNNM2 and provide basic foundations for more accurate genetic counseling.